Multisystem Inflammatory Syndrome in Children (MIS-C): A Brazilian epidemiological analysis (Research, Society and Development, 2021)
This article aimed to analyze the Brazilian epidemiological context of pediatric multisystemic inflammatory syndrome (MIS-C) temporally associated with Covid-19. Therefore, a statistical and descriptive study was carried out, guided by the interpretation of data collected on the platforms of the Health Departments of the 27 federative units in the country and covering the period between the first confirmed case of the syndrome, in 2020, until june 2021. The parameters investigated were about the total number of cases and deaths, as well as the distribution between states, sexes and age groups. There were 1010 diagnoses and 65 deaths triggered by the syndrome, indicating a fatality rate of 6.4%. 55.4% of the cases were described in males, while deaths, in turn, were more common in girls, representing approximately 76% of the verified deaths. The age group most affected by SIM-P was between 0 and 4 years of age. Most cases and deaths caused by the syndrome occurred in the Southeast region, especially in the state of São Paulo, which accounted for 19.1% of all diagnoses and 18.4% of all deaths in Brazil. SIM-P represents a serious condition associated with SARS-CoV-2 infection and, therefore, requires caution on the part of children, adolescents and their families regarding the proper adoption of preventive measures recommended for Covid-19. Although this is a recent topic, the numbers already reported in the country are sufficient for pediatricians and general practitioners to obtain the necessary medical knowledge for the early diagnosis of this syndrome, allowing for the reduction of negative outcomes and a better prognosis.